Whispering in the Dark Faint X-Ray Emission from Black Holes with Ob Star Companions - El Mellah, I (EDP Sciences, 2024)
Context. Recently, astrometric and spectroscopic surveys of OB stars revealed a few stellar-mass black holes (BHs) with orbital periods of as low as 10 days. Contrary to wind-fed BH high-mass X-ray binaries (HMXBs), no X-ray counterpart was detected, probably because of the absence of a radiatively efficient accretion disc around the BH. Nevertheless, dissipative processes in the hot, dilute, and strongly magnetised plasma around the BH (so-called BH corona) can still lead to non-thermal X-ray emission (e.g. synchrotron). Aims. We determine the X-ray luminosity distribution from BH+OB star binaries up to orbital periods of a few thousand days. Methods. We used detailed binary evolution models computed with MESA for initial primary masses of 10–90 M and orbital periods of 1–3000 d. We computed the X-ray luminosity for a broad range of radiative efficiencies that depend on the mass accretion rate and flow geometry. Results. For typical conditions around stellar-mass BHs, we show that particle acceleration through magnetic reconnection can heat the BH corona. A substantial fraction of the gravitational potential energy from the accreted plasma is converted into non-thermal X-ray emission. Our population synthesis analysis predicts that at least 28 (up to 72) BH+OB star binaries in the Large Magellanic Cloud (LMC) produce X-ray luminosities of above 1031 erg s−1, which are observable with focused Chandra observations. We identify a population of SB1 systems in the LMC and HD96670 in the Milky Way comprising O stars with unseen companions of masses of above 2.3 M , which aligns well with our predictions and may be interesting sources for follow-up observations. The predicted luminosities of the OB companions to these X-ray-emitting BHs are 104.5−5.5 L . Conclusions. These findings advocate for prolonged X-ray observations of the stellar-mass black hole candidates identified in the vicinity of OB stars. Such long exposures could reveal the underlying population of X-ray-faint BHs and provide constraints for the evolution from single to double degenerate binaries and identify the progenitors of gravitational wave mergers. © The Authors 2024.
Keywords: stars: black holes; stars: evolution; stars: massive; X-rays: binaries